Media Pembelajaran Video Animasi Dan Gambar Ilustrasi Dalam Meningkatkan Hasil Belajar Bola Basket Kelas XI SMK Negeri 1 Semarang - Hendrasswari, Bayu Peni; Ardiyanto, Asep; Suharso, Suharso (Universitas PGRI Semarang, 2025)
This research aims to examine the influence and differences of the use of learning media, animated videos and illustrations in improving the learning outcomes of basketball class XI SMK Negeri 1 Semarang. This quantitative research was carried out in the form of two groups of tests before and after. The research sample was 60 students in grade XI of SMK Negeri 1 Semarang. Prerequisite tests for normality and homogeneity were used in the analysis of this study. The results of the study showed that the average score of the students in the Animation Video learning approach group was 44.2 and the posttest results after treatment with Animation Video learning were on average 85. Meanwhile, the data of the problem basin learning group before the treatment was carried out, the average student score was 75 and after the treatment, the student score changed, namely with a mean value or an average score of 85. Mann-Whitney test with a baseline of Asymp values. Sig 0.05, then the hypothesis is accepted. The results of the hypothesis analysis of the SPSS software application assistance above can be concluded that based on the hypothesis test with a significance value of 0.112 or 0.05. It was interpreted that the hypothesis was rejected because there was no significant difference in the results of the students' pretest between the two treatment groups. The use of the Animation Video and Illustration Learning Model has a significant influence on basketball learning outcomes in grade XI students of SMK Negeri 1 Semarang as seen from the comparison of significance values with significant norm references. In the Animation Video learning model group, it provided an increase of 12.2% while the Illustration learning model group provided an increase of 9.9%. This means that the Animated Video learning model group is an effective learning model compared to the animated video learning model on basketball learning outcomes in grade XI students of SMK Negeri 1 Semarang. Based on the results of the research that has been carried out, the Animation Video learning model is an effective learning model compared to the animation video learning model on basketball learning outcomes in grade XI students of SMK Negeri 1 Semarang.